Parameters of ventricular repolarization in patients with autoimmune hepatitis - Burak Açar; Mahmut Yüksel; Çağrı Yayla; Özgür Kırbaş; Sefa Ünal; Ahmet Göktuğ Ertem; Koray Demirtaş; Mustafa Kaplan; Meral Akdoğan; Sabite Kaçar; Ertuğrul Kayaçetin; Sinan Aydoğdu (KARE Publishing, 2017)
Objective: Autoimmune hepatitis (AIH) is a liver disorder that affects both children and adults. It is characterized by inflammatory liver histology, elevated transaminase level, circulating nonorgan-specific autoantibodies, and increased level of immunoglobulin G in the absence of known etiology. Ventricular repolarization has been evaluated using T wave and QT interval measurements in patients with hepatic cirrhosis. Ventricular repolarization may be defined using QT interval, QT dispersion, and T wave measurements. Recently, it has been demonstrated that peak and end of the T wave (Tp-e) interval, Tp-e/QT, and Tp-e/corrected QT interval (QTc) ratios can be novel indicators for prediction of ventricular arrhythmias and mortality. In this study, an investigation of ventricular repolarization using Tp-e interval and Tp-e/QT ratio in patients with AIH was performed. Methods: Total of 31 patients with AIH and 31 controls were enrolled in the present study. Tp-e interval, Tp-e/QT, and Tp-e/QTc ratios were measured on 12-lead electrocardiogram. Results: QT interval (378.9+-41.4 vs. 350.0+-22.7; p=0.001), QTc interval (396.8+-46.7 vs. 367.3+-34.9; p=0.039), Tp-e interval (68.2+-12.3 vs. 42.5+-6.8; p<0.001), Tp-e/QT ratio (0.18+-0.02 vs. 0.12+-0.01; p<0.001) and Tp-e/QTc ratio (0.17+-0.02 vs. 0.11+-0.01; p<0.001) were significantly higher in patients with AIH than control patients. Conclusion: The results of the present study indicated that Tp-e interval, Tp-e/QT, and Tp-e/QTc ratios were greater in patients with AIH.